Using a 3-D MHD simulation to interpret propagation and evolution of a coronal mass ejection observed by multiple spacecraft: The 3 April 2010 event - Zhou, Yufen; Feng, Xueshang; Zhao, Xinhua (Journal of geophysical research. Space physics, 2014)
The coronal mass ejection (CME) event on 3 April 2010 is the first fast CME observed by STEREO Sun Earth Connection Coronal and Heliospheric Investigation/Heliospheric Imager for the full Sun‐Earth line. Such an event provides us a good opportunity to study the propagation and evolution of CME from the Sun up to 1 AU. In this paper, we study the time‐dependent evolution and propagation of this event from the Sun to Earth using the 3‐D SIP‐CESE (Solar‐InterPlanetary Conservation Element and Solution Element) MHD model. The CME is initiated by a simple spherical plasmoid model: a spheromak magnetic structure with high‐speed, high‐pressure, and high‐plasma density plasmoid. The simulation performs a comprehensive study on the CME by comparing the simulation results with STEREO and Wind observations. It is confirmed from the comparison with observations that the MHD model successfully reproduces many features of both the fine solar coronal structure and the typical large‐scale structure of the shock propagation and gives the shock arrival time at Earth with an error of ∼2 h. Then we analyze in detail the several factors affecting the CME's geo‐effectiveness: the CME's propagation trajectory, span angle, and velocity. Key Points The time‐dependent propagation of CME from the Sun to Earth The analysis of the propagation velocity, shape, and trajectory of the CME The comparison of the simulation results with STEREO and Wind observations